2005
DOI: 10.3168/jds.s0022-0302(05)73068-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Dried Whey Protein Concentrate and Isolate Flavor

Abstract: The flavor of whey protein concentrates (WPC 80) and whey protein isolates (WPI) was studied using instrumental and sensory techniques. Four WPC 80 and 4 WPI, less than 3 mo old, were collected in duplicate from 6 manufacturers in the United States. Samples were rehydrated and evaluated in duplicate by descriptive sensory analysis. Duplicate samples with internal standards were extracted with diethyl ether. Extracts were then distilled to remove nonvolatile material using high vacuum distillation. Volatile ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
168
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 124 publications
(180 citation statements)
references
References 47 publications
(100 reference statements)
12
168
0
Order By: Relevance
“…It is likely that the higher lactose and fat content (Table 4) of the WPC samples led to more Maillard reaction and lipid oxidation product formation. All sample pairs, with the exception of mozzarella WPC and WPI, had between 4 and 11 fewer compounds detected for WPI products; Carunchia Whetstine et al (2005) also reported fewer compounds derived from lipid oxidation in WPI as compared with WPC. Additionally, the MF and UF procedures during WPI manufacture were not only methods of whey component fractionation, but also probable sources of volatile loss.…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…It is likely that the higher lactose and fat content (Table 4) of the WPC samples led to more Maillard reaction and lipid oxidation product formation. All sample pairs, with the exception of mozzarella WPC and WPI, had between 4 and 11 fewer compounds detected for WPI products; Carunchia Whetstine et al (2005) also reported fewer compounds derived from lipid oxidation in WPI as compared with WPC. Additionally, the MF and UF procedures during WPI manufacture were not only methods of whey component fractionation, but also probable sources of volatile loss.…”
Section: Resultsmentioning
confidence: 87%
“…Based on prior research (Carunchia Whetstine et al, 2005;Gallardo-Escamilla et al, 2005b), we had expected to find more differences within the WPC and WPI groups due to the different cheese types and processing methodologies. One reason for the lack of these differences may be because we processed, spray dried, and stored all the wheys under the same controlled conditions in our pilot plant (except for IEX) and thus removed many sources of variability.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations